Pengaruh Murottal Al-Quran Terhadap Kualitas Tidur Lansia - Kresno Aji Priambodo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study examines the effect of listening to Quranic murottal on the quality of sleep of the elderly. Quality sleep is important for physical and mental health, especially for the elderly who often experience sleep disorders. The approach used was a qualitative method with a case study, in which in-depth interviews were conducted with five elderly people who routinely listened to Al-Quran murottal before going to bed. Respondents were aged between 60-74 years. The results showed that listening to Quranic murottal significantly improved the quality of sleep of the elderly. They reported feeling calmer, more relaxed and slept better after listening to the murottal. This study reveals that Quranic murottal can be an effective non-pharmacological therapy to improve the sleep quality of the elderly. Further research with larger samples and quantitative methods is needed to measure the effectiveness of this therapy more objectively.